Fertilization using sewage sludge in unfertile tropical soils increased wood production in Eucalyptus plantations - Abreu-Junior, Cassio Hamilton; Firme, Lucia Pitol; Baca Maldonado, Carlos Alberto; Moraes Neto, Sebastiao Pires de; Alves, Marcelo Correa; Muraoka, Takashi; Boaretto, Antonio Enedi; Gava, Jose Luis; He, Zhenli; Rodrigues Nogueira, Thiago Assis [UNESP]; Capra, Gian Franco (Elsevier B.V., 2017)
Fertilization of Eucalyptus plantations using sewage sludge on unfertile tropical soils represents an alternative to using mineral N and P fertilizers. A 44-month field experiment was conducted to study the effects of increasing application of sludge, and its interactions with mineral N and P fertilizers, on wood volume. Four rates of sludge (0, 8,15 and 23 Mg ha(-1), dry base), N (0, 47, 95 and 142 kg ha(-1)) and P (0, 28, 56 and 84 kg ha(-1) of P2O5) were combined in a 4 x 4 x 4 factorial scheme in a totally randomized block design. Response surface and age-shift modeling was used to establish an initial recommendation for mineral fertilization of the Eucalyptus plantations treated with sludge and to analyze the implications of increased growth on the duration of the forest cycle in a tropical climate. The results showed that from 8 to 44 months after planting, the sludge application (with or without N and P) yielded a statistically larger wood volume (P < 0.05), compared to application of N and P fertilizers only. The response surface modeling showed the following outcomes: i) application of sludge based on N criterion reduced the need for N and P fertilizers by 100%; and ii) an increase in wood volume by 7% could be achieved, compared to NPK fertilizers only, if 2/3 of the recommended P was applied. The cultivation time to produce 150 m(3) ha(-1) of wood volume was 45 months for the control and was reduced by two, three, four, or five months, respectively, through application of recommended P, sludge dose, sludge plus one third of P, and sludge plus two thirds of P. On the whole, sewage sludge could represent an excellent unconventional N and P fertilizer source for wood production on unfertile tropical soils. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Biosolid; Eucalypt; Planted forest; Organic fertilizer; Unfertile tropical soils